2011
DOI: 10.1177/009102601104000104
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Training: Person versus Machine

Abstract: Computer-based training is rapidly being implemented in organizations. Many advantages of this approach have been suggested (e.g., self-paced instruction, uniform content, and long-run cost efficiency) along with several potential disadvantages (e.g., noncompletion rates, computer availability). Despite the purported advantages of computer-based training, little research has examined the effect of computer-based training on learning. This field study systematically compared computer-based sexual harassment tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In addition, several studies found no change in attitude (Kearney et al, 2004;Magley et al, 2013, Study 2;Preusser et al, 2011).…”
Section: Attitudesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, several studies found no change in attitude (Kearney et al, 2004;Magley et al, 2013, Study 2;Preusser et al, 2011).…”
Section: Attitudesmentioning
confidence: 98%
“…The 12 studies that investigate the effect of training design features on one or more training outcomes are summarized in Table . Of the nine experimental studies, four purport to test the effect of different instructional media (Birdeau et al, ; Bonate & Jessell, ; Pilgram & Keyton, ; Preusser, Bartels, & Nordstrom, ). However, all four appear to confound the effect of instructional media with the effect of instructional content or methods.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…One major influence on outcomes is duration of training, which has varied in research studies from 1 to 2 h [29,30] to well over 8 hours [31][32][33]. Kalinoski et al [13] found diversity trainings lasting longer than 4 h tended to have larger effects on affective outcomes than did shorter trainings.…”
Section: Designmentioning
confidence: 99%
“…That said, very few studies have used computer-based training programs and none of the studies included by Kalinoski et al used a blended learning approach as was used by Rudstam et al [26]. Preusser et al [30] conducted the only known direct comparison of these training delivery methods. The computer-based training took 1.5-2 h to complete and contained four sections.…”
Section: Designmentioning
confidence: 99%